Protective effects of β-glucan as adjuvant combined inactivated Vibrio harveyi vaccine in pearl gentian grouper. Issue 106 (November 2020) - Wei, Guangben; Tan, Huiming; Ma, Shaohong; Sun, Guorong; Zhang, Yilin; Wu, Yuanzhi; Cai, Shuanghu; Huang, Yucong; Jian, Jichang
Abstract: Vaccination is one of the strategies for preventing Vibrio harveyi infection in marine-cultured animals. In this study, we prepared a formalin-killed cells of V. harveyi ZJ0603 vaccine (FKC) combined with β-glucan to immune pearl gentian grouper. The results indicated that the expression levels of IgM, TNF-α, MHC-Iα, IL-1β and IL-16 significantly increased in the spleen of the vaccinated fish. Antibody titers, activities of lysozyme and superoxide dismutase were significantly prompted in blood of the vaccinated fish. After 35 d post-vaccination, all fish were challenged intraperitoneally by virulent V. harveyi, and the relative percentage of survival (RPS) of FKC+β-glucan, FKC, β-glucan and PBS were 68 ± 5.7%, 55 ± 8.5%, 42 ± 7.5% and 32 ± 6.9%, respectively. These results demonstrated that β-glucan could be as a potential adjuvant of FKC and provide good protective effect against V. harveyi infection in the pearl gentian grouper culture. Highlights: Vibrio harveyi formalin-killed cells (FKC) vaccine are evaluated the immune responses and protective effect by combined with β-glucan in pear gentian grouper for the first time. The accumulated relative percent survival (RPS) of fishes were significantly improved when β-glucan as adjuvant to used. Immune-related genes were remarkably higher expression level of combined with adjuvant group in post-vaccination compared with only used of vaccine, adjuvants or PBS. Antibody titers, lysozyme and superoxide dismutase were significantly elevated in the vaccinated fish.